2020
DOI: 10.1371/journal.pone.0237714
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of different virulent factors in methicillin-resistant Staphylococcus aureus isolates recovered from Iraqis and Syrian refugees in Duhok city, Iraq

Abstract: Methicillin-resistant Staphylococcus aureus (MRSA) is a serious public health problem. There is limited information regarding the genetics of MRSA strains among the native Iraqi and incoming Syrian refugee communities. We aimed to characterize the genotypes and different virulence factors of MRSA in strains isolated from these two communities. Frozen MRSA strains (125) isolated from the native Iraqi and Syrian refugee communities were used in this study. PCR (singleplex and multiplex) and agr typing was used f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 29 publications
1
19
3
Order By: Relevance
“…Sterile swabs were collected from the anterior nares of the subjects. The swabs were firstly moistened with sterile normal saline and then rolled briefly in both nostrils for a few second by about 2 to 3 cm (Rasheed and Hussein, 2020d). Swabs were directly sent to the microbiological laboratory after being inoculated with Brain Heart Infusion (BHI) broth (Neogene, UK).…”
Section: Sampling and Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sterile swabs were collected from the anterior nares of the subjects. The swabs were firstly moistened with sterile normal saline and then rolled briefly in both nostrils for a few second by about 2 to 3 cm (Rasheed and Hussein, 2020d). Swabs were directly sent to the microbiological laboratory after being inoculated with Brain Heart Infusion (BHI) broth (Neogene, UK).…”
Section: Sampling and Data Collectionmentioning
confidence: 99%
“…Moreover, usage of equipment that causes skin abrasion, and poor sanitation are also risk factors for S. aureus infection in sports (Grosset-Janin et al, 2012). Several antibiotics have been developed resistance to S. aureus in our region (Rasheed and Hussein, 2020a, Naqid et al, 2020b, Naqid et al, 2020a and methicillin-resistant S. aureus (MRSA) have also reported among hospitalized patients (Abdulkareem et al, 2020, Hussein et al, 2017, and the community (Hussein et al, 2019, Rasheed andHussein, 2020d). The prevalence of community-associated MRSA among athletes is higher particularly those people participate in direct contact sports (Rice et al, 2008), even three times greater when compared to the general community (Graham et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Other virulence factors include Panton-Valentine leucocidin (PVL), encoded by the lukS/F-PV and lukE/D genes, exfoliative toxins (ETs) (Ladhani, 2001;Rasheed and Hussein, 2020), arginine catabolic mobile element (ACME, arcA), β-hemolysin (hlb), TSST-1, accessory gene regulator (agr), and α-hemolysin (hla) (Yarwood et al, 2004;Scherr et al, 2015). This review aims to provide an understanding of the mechanism of exotoxins and the molecular characteristics of S. aureus, focusing on MRSA strains and summarizing the current epidemic and virulence factors of MRSA.…”
Section: Reviewmentioning
confidence: 99%
“…Wars and human crises contribute to infectious disease spread among various regions and countries, in turn leading to changes in the global infection map [ 9 ]. Northern cities of Iraq received thousands of refugees that fled from areas experiencing conflict to neighbouring countries during the Syrian war [ 10 , 11 ]. A previous study revealed that the prevalence of HBV was 3.86% among pregnant refugees, a rate higher than that of the host community of Duhok (1.09%) [ 9 ].…”
Section: Introductionmentioning
confidence: 99%